A Highly Sensitive and Cost‐Effective Flexible Pressure Sensor with Micropillar Arrays Fabricated by Novel Metal‐Assisted Chemical Etching for Wearable Electronics. Issue 9 (5th August 2019) - Zhang, Xinyu; Hu, Yougen; Gu, Han; Zhu, Pengli; Jiang, Wenlong; Zhang, Gang; Sun, Rong; Wong, Ching‐Ping
Abstract: As one of the most significant constituent parts of wearable electronic systems, flexible pressure sensors can accommodate irregular surfaces and perform spatial mapping when subjected to external pressure or strain stimuli. Herein, a wearable flexible pressure sensor integrated with two interlocked micropillar arrays is demonstrated by a facile and cost‐effective metal‐assisted chemical etching (MaCE) method with the assistance of polymer microspheres lithography technique. The flexible sensor, with micropillars of 2.6 µm in diameter, 6.6 µm in height, and 3 µm in pitch, exhibits superior sensitivity of −4.48 kPa −1 (0–100 Pa), rapid response and relaxation time of 52 and 40 ms, respectively, low detection limit of <1 Pa, and outstanding working stability over 5000 cycles of pressure loading/unloading. The prepared sensors are successfully demonstrated in detecting finger motions and monitoring human pulse signals, paving the promising route for its function in wearable electronic skins, soft robotics, and healthcare monitoring devices, etc. Abstract : A flexible pressure sensor with face‐to‐face interlocked micropillar arrays is fabricated by a novel and cost‐effective metal‐assisted chemical etching method with assistance of polymer microspheres lithography technique, which exhibits high sensitivity, fast response, low detection limit, and excellent working stability, and demonstrates promising potential in monitoring human body motions and physiological signals.